Dissociation between muscle tricarboxylic acid cycle pool size and aerobic energy provision during prolonged exercise in humans - Gibala, Martin J (Blackwell Science Inc, 2002)
It has been suggested that a decrease in the total concentration of tricarboxylic acid cycle intermediates (TCAIs) - secondary to a reduction in glycogen availability - compromises oxidative energy provision in skeletal muscle during prolonged exercise. However, no study has directly tested this hypothesis. We therefore studied six men (28 ± 2 years) during 90 min of leg kicking exercise at an intensity equivalent to 70 % of maximum. Biopsies (vastus lateralis) were obtained at rest and after 5, 10, 15, 30, 60 and 90 min of exercise, and thigh oxygen uptake (V(O(2,thigh))) was calculated according to the Fick principle. The sum of six measured TCAIs (≈95 % of total pool size) was 1.30 ± 0.15 mmol (kg dry wt)(−1) at rest and increased (P ≤ 0.05) rapidly during exercise to a peak value of 3.15 ± 0.23 mmol (kg dry wt)(−1) after 10 min. Thereafter, the [TCAI] declined to 2.14 ± 0.23, 1.73 ± 0.32 and 1.62 ± 0.10 mmol (kg dry wt)(−1) after 30, 60 and 90 min, respectively (P ≤ 0.05vs.10 min). Despite the 50 % decrease in [TCAI], aerobic energy provision was not compromised, as evidenced by stable V(O(2))(,thigh) values throughout the entire exercise bout and little change in muscle [phosphocreatine] after 10 min. The largest decrease in [TCAI] (Δ + 1.00 ± 0.24 mmol (kg dry wt)(−1)) occurred from 10 to 30 min of exercise despite the fact that muscle [glycogen] remained relatively high at this point in exercise (≈274 ± 24 mmol (kg dry wt)(−1) after 30 min; ≈65 % of rest value). Conversely, there was little change in [TCAI] during the final 30 min of exercise (Δ + 0.11 ± 0.29 mmol (kg dry wt)(−1)) despite a decrease in [glycogen] to ≈72 ± 3 mmol (kg dry wt)(−1) after 90 min (≈13 % of rest value). We conclude that there is a progressive decrease in muscle [TCAI] during prolonged exercise in humans; however this decrease does not compromise aerobic energy provision and is not attributable to the depletion of muscle [glycogen].